Notes on the Systematics, Geographic Distribution and Biology of the Sandy Shore Crab, Matuta Lunaris (Forskal) - Perez, Orpha S. (Silliman Journal, 2024)
The systematics, geographic distribution, diet and reproductive biology of M. lunaris are described. These aspects are discussed in relation to M. lunaris as a surf zone species and as a food source in a subsistence economy such as that of the Philippines.